Diversidade de anfíbios anuros em campos de altitute dos estados de Santa Catarina e Paraná - Assmann, Bruna Raquel (2015)
Threats to biodiversity in countryside areas are growing in an accelerated rhythm. Researches aiming biodiversity inventory and habitat requirements in these areas are necessary in the pursuit of public policies for the conservation of this diversity. In the present study we determined the wealth and the spatial distribution of the anuran fauna in high altitude fields of Santa Catarina and Paraná. So we: (1) described the composition and wealth in the communities studied; (2) tested whether the local variables of water bodies, space and landscape are determinants of species richness; (3) tested whether environmental heterogeneity influences the structure of the anuran community; (4) tested whether anuran species have segregation or overlap in vocalization sites, and (5) we verified that local variables best discriminate the species found. The samples were collected from October to November 2013, using the method of 'search in breeding sites' by adults in vocalization activity and tadpoles’ collection as well as the characterization of the vocalization sites. In this effort, we sampled 47 water bodies (puddles) on the anuran fauna, environmental descriptors being recorded in three scales: local (puddles structure), spatial (spatial proximity) and landscape (matrix representativeness type). We recorded the occurrence of 22 anuran species in the altitude fields studied, 18 species recorded by finding males in vocalization activity, and 20 species were recorded in the larval stage. We used generalized regression patterns considering the sets of descriptors as possible predictors of anuran species richness and finally, we used a Canonical Redundancy Analysis to explore the role of environmental descriptors on the anuran species density in puddles. We used a Generalized Discriminant Analysis to identify which subsets of vocalization sites predictors better discriminate the anuran species, testing the most important scale (if habitat or microhabitat). The richness of anurans in puddles was determined by local variables represented by the puddles hydro period, the emergent vegetation cover and the percentage of stones on the shore. The adult density was correlated with the percentage of vegetation cover on the puddles banks, and the tadpoles’ density was related to the banks vegetation cover, the puddles area and a landscape variable (farming presence on the bank). The best variables sets that distinguished the anuran species were related to the micro-habitat scale: interaction of substrate type, bank distance, water depth and perch height, as well the substrate type considered isolatedly. The local and landscape predictors were important for the distribution of amphibians in the studied countryside areas. Our data is necessary on the pursuit of public policies for biodiversity conservation of the countryside areas threatened by anthropic actions.